PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BADAN PUSAT STATISTIK KABUPATEN OGAN ILIR - Tutik Pebrianti; Imam Suroso (Jurnal Manajemen Kompeten, 2018)
This study entitled " the effect of motivation and job satisfaction toward job performance of Badan Pusat Statistik employees Ogan Ilir regency”. Population is used in this study is 31 persons employees of Badan Pusat Statistik Ogan Ilir regency and all of population is as sample, too by consideration that all the employees have more than two years working period and they have status as civil servants. Sampling technique used saturated sampling. Partially research result showed that motivation has no significantly effect towards employees job performance but in contrast job satisfaction has a partially significanteffect Towards empolyees job performance of Badan Pusat Statistik Ogan Ilir regency with f obtained value is 10.295 andR square value is 0.433 (43.3%) with multiple regression equation:Y=6.619 + 0,256X1 + 0,3X2 + e. While dominant variable which is influence Badan Pusat Statistik employees' job performance in Ogan Ilir regency is job satisfaction variable by significant valUe (p=0.05 and b=0.3). If the employees' job satisfaction is high so organization performance will be good and vice versa.